2020
DOI: 10.1155/2020/8863724
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Deep Learning Method with Attention-Based LSTM Model for Short-Term Traffic Speed Forecasting

Abstract: Short-term traffic speed prediction is a promising research topic in intelligent transportation systems (ITSs), which also plays an important role in the real-time decision-making of traffic control and guidance systems. However, the urban traffic speed has strong temporal, spatial correlation and the characteristic of complex nonlinearity and randomness, which makes it challenging to accurately and efficiently forecast short-term traffic speeds. We investigate the relevant literature and found that although m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Nevertheless, while the prediction of MSTFLN is in hours, the prediction of the CNN-LSTM model is restricted to dozens of minutes. Very good results for the short-term prediction were found by the authors of [51], who presented the attention-based LSTM (ATT-LSTM) model for short-term traffic speed forecasting. The average MAE of their ATT-LSTM model was 3.26 km/h for 15 min prediction.…”
Section: Discussion and Future Directionsmentioning
confidence: 97%
“…Nevertheless, while the prediction of MSTFLN is in hours, the prediction of the CNN-LSTM model is restricted to dozens of minutes. Very good results for the short-term prediction were found by the authors of [51], who presented the attention-based LSTM (ATT-LSTM) model for short-term traffic speed forecasting. The average MAE of their ATT-LSTM model was 3.26 km/h for 15 min prediction.…”
Section: Discussion and Future Directionsmentioning
confidence: 97%
“…Aniekan et al [21] proposed a bi-directional Long Short-Term Memory Neural Network (LSTM-NN) model and combined it with weather data to predict the short-term traffic speed of the main road through Manchester. Wu et al [22] combined LSTM with an attention mechanism to create the ATT-LSTM model and applied it to road traffic speed prediction in Shenzhen. Results showed that the attention mechanism greatly improved prediction accuracy.…”
Section: Related Researchmentioning
confidence: 99%
“…In addition, they have been proven to encounter poor performance compared to nonparametric methods in unstable traffic conditions and complex road settings [12,13]. Neural network (NN), K-nearest neighbors (KNN) [14], Bayesian network (BN) [15], and support vector machine (SVM) [10,16] are the representatives of nonparametric algorithms [17]. Such approaches were advantageous as they are free of assumptions regarding the underlying model formulation and the uncertainty in estimating the model parameters [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches were advantageous as they are free of assumptions regarding the underlying model formulation and the uncertainty in estimating the model parameters [18]. Recently, studies using deep learning techniques have been conducted to improve the prediction accuracy of traffic conditions [17,19]. ese include long short-term memory (LSTM) [20,21], deep belief network (DBN) [22], stacked autoencoder (SAE) [23,24], and convolutional neural network (CNN) [25], which were widely used and had achieved good results in predicting traffic conditions [26].…”
Section: Introductionmentioning
confidence: 99%